1994
DOI: 10.1111/j.1442-200x.1994.tb03222.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Plesiomonas shigelloides septicemia and meningitis: A case and review

Abstract: A 3 day old neonate with septicemia and meningitis due to Plesiomonas shigelloides is described. We could not detect the source of this infection. The patient was treated with cefotaxime and survived without sequelae. Nine previously reported cases with this infection were reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2000
2000
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Infections with P. shigelloides have been strongly associated with drinking untreated water [59,60], eating uncooked shellfish or with travel to developing countries [61,62]. Recent studies have suggested that P. shigelloides is an opportunistic pathogen in immunocompromized hosts [63] especially neonates [64]. It has been associated with diarrhoeal illness [65] and other diseases in normal hosts as well.…”
Section: Structure Of Carbohydrate Antigens Of Gammaproteobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Infections with P. shigelloides have been strongly associated with drinking untreated water [59,60], eating uncooked shellfish or with travel to developing countries [61,62]. Recent studies have suggested that P. shigelloides is an opportunistic pathogen in immunocompromized hosts [63] especially neonates [64]. It has been associated with diarrhoeal illness [65] and other diseases in normal hosts as well.…”
Section: Structure Of Carbohydrate Antigens Of Gammaproteobacteriamentioning
confidence: 99%
“…Plesiomonas shigelloides has been isolated from a variety of clinical specimens including cerebrospinal fluid, wounds and the respiratory tract. Reported cases of meningitis and bacteraemia [64] caused by P. shigelloides are of special interest because of their seriousness. P. shigelloides causes both localized infections originating from infected wounds and gastrointestinal infections, which can disseminate to other parts of the body [66].…”
Section: Structure Of Carbohydrate Antigens Of Gammaproteobacteriamentioning
confidence: 99%
“…Extraintestinale Infektionen sind selten; sie sind als Bakteriämie, Meningitis [5,7,10,16,18] und in sehr seltenen Fällen auch als Endophthalmitis, Osteomyelitis oder septische Arthritis publiziert worden [1,6,9,10,13]. Intestinale Infektionen verlaufen meist als Diarrhö, selten auch als Peritonitis oder perirektale Infektion.…”
unclassified
“…Eine besondere Suszeptibilität von Immunsupprimierten für Plesiomonas-Infektionen ist wahrscheinlich. Des Weiteren wurden einzelne Fälle von spontaner bakterieller Peritonitis, Polyarthritis, Kompartmentsyndrom und Zellulitis, postoperativem Pankreasschwanzabszess, akuter Cholezystitis, Cholangiosepsis, pseudomembranöser Kolitis und Pseudoappendizitis beschrieben [1,6,9,10,13,20].…”
unclassified
“…Infections with P. shigelloides have been strongly associated with drinking untreated water [2,3], eating uncooked shellfish or with travel to developing countries [4,5]. Recent studies have suggested that P. shigelloides is an opportunistic pathogen in immunocompromised hosts [6] especially neonates [6–10]. It has been associated with diarrhoeal illness [11] and other diseases in normal hosts as well.…”
mentioning
confidence: 99%